Photocatalytic Oxidation Reactions Mediated by Covalent Organic Frameworks and Related Extended Organic Materials - Alemán, José; Mas-Ballesté, Rubén (Frontiers in Chemistry, 2021)
Covalent Organic Frameworks (COFs) have been widely used as photocatalysts in the last few years. Such interest arises from the wide range of covalent linkages employed in their construction, which offer many possibilities to design extended frameworks and to link photoactive building blocks. Thus, the potential utility of predesigned organic photoactive fragments can be synergistically added to the inherent advantages of heterogeneous catalysis, such as recyclability and easy separation of catalyst. In this overview, the current state of the art on the design of COFs for photocatalytic oxidation reactions will be presented. The designing process of COFs is usually conditioned by the generally accepted concept that crystallinity and porosity defines the quality of the materials obtained. The care for the structural integrity of materials obtained is understandable because many properties and applications are intimately related to these features. However, the catalytic activity does not always directly depends on these characteristics. A critical compilation of the available literature is performed in order to offer a general perspective of the use of COFs in photocatalytic oxidation processes, including water oxidation, which constitute an important outcome relevant to artificial photosynthesis.